Metal Coordination and Biological Screening of a Schiff Base Derived from 8-Hydroxyquinoline and Benzothiazole - Nádia Ribeiro; Pedro F. Farinha; Jacinta O. Pinho; Hugo Luiz; János P. Mészáros; Adelino M. Galvão; João Costa Pessoa; Éva A. Enyedy; Catarina Pinto Reis; Isabel Correia; Maria Manuela Gaspar (MDPI AG, 2022)
Designing new metallodrugs for anticancer therapy is a driving force in the scientific community. Aiming to contribute to this field, we hereby report the development of a Schiff base (H2L) derived from the condensation of 2-carbaldehyde-8-hydroxyquinoline with 2-hydrazinobenzothiazole and its complexation with transition metal ions. All compounds were characterised by analytical and spectroscopic techniques, which disclosed their structure: [Cu(HL)Cl], [Cu(HL)2], [Ni(HL)(acetate)], [Ni(HL)2], [Ru(HL)Cl(DMSO)], [VO(HL)2] and [Fe(HL)2Cl(H2O)]. Different binding modes were proposed, showing the ligand's coordination versatility. The ligand proton dissociation constants were determined, and the tested compounds showed high lipophilicity and light sensitivity. The stability of all complexes in aqueous media and their ability to bind to albumin were screened. Based on an antiproliferative in vitro screening, [Ni(HL)(acetate)] and [Ru(HL)Cl(DMSO)] were selected for further studies aiming to investigate their mechanisms of action and therapeutic potential towards colon cancer. The complexes displayed IC50 < 21 μM towards murine (CT-26) and human (HCT-116) colon cancer cell lines. Importantly, both complexes exhibited superior antiproliferative properties compared to the clinically approved 5-fluorouracil. [Ni(HL)(acetate)] induced cell cycle arrest in S phase in CT-26 cells. For [Ru(HL)Cl(DMSO)] this effect was observed in both colon cancer cell lines. Additionally, both compounds significantly inhibited cell migration particularly in the human colon cancer cell line, HCT-116. Overall, the therapeutic potential of both metal complexes was demonstrated.